Pencak Silat Tapak Suci: Overview in a Historical Perspective of Muhammadiyah Autonomic Organizations in Indonesia - Oman Hadiana; Herman Subarjah; Amung Ma’mun; Mulyana Mulyana; Didik Rilastiyo Budi; Adi Rahadian (STKIP Muhammadiyah Kuningan, 2022)
Pencak Silat is a cultural heritage of the archipelago that needs to be preserved. There are several Pencak silat colleges spread across Indonesia, and one of them is the martial art of Pencak silat, the tapak suci of the son of Muhammadiyah. The purpose of this study is to describe the history of Pencak silat Tapak Suci as part of the autonomous Muhammadiyah organization in Indonesia. The research method that we use is ethnographic qualitative. The research was carried out for six months, starting from the beginning of June to December 2021. The data collection technique was structured interviews with the supervisory board, trainers, and administrators who could provide representative information. The results showed that the forerunner of the birth of the tapak suci silat in Kauman village, Yogyakarta, was in 1963. Its spread started from the regional and national to foreign countries such as Malaysia, Brunei Darussalam, Turkey, and Germany. The conclusion of this study states that Tapak Suci teaches not only basic moves and techniques but also Islamic values ​​such as worship, aqidah, and morality. The philosophical meaning of the Tapak Suci movement comes from a cultural heritage passed down from generation to generation, and some come from animal movements.